A Fruitful Crisis of Belief: Hans Jonas on a Proper Mode of Faith within the Context of Modernity - Pietropaoli, Matthew (Proceedings of the American Catholic Philosophical Association, 2017)
The philosopher Hans Jonas penned several essays illustrating how modern thought represents a revolutionary overturning of previously held religious beliefs. The new paradigms of thought toppled prior worldviews of Christianity. Thus, modernity represents a crisis for religious belief. Yet, Jonas contends that modern thought may paradoxically provide the occasion for a deeper encounter with God. This paper will examine Jonas's discussions on both the challenge and opportunity which modern thought presents to Christianity. First, I will address Jonas's understanding of how modern science transformed the Christian, God-centered view of the universe, showing, instead, a world following from impersonal laws. Second, I look briefly at Jonas's understanding of how Rudolph Bultmann responded to this crisis by attempting to "de-mythologize" belief. Third, I will show how Jonas argues that the challenge of modern science to Christian cosmology allows the believer the opportunity for a closer connection to God, moving beyond beliefs and into relationship.